Behavioral responses of Anagrus nilaparvatae to common terpenoids, aromatic compounds, and fatty acid derivatives from rice plants. Issue 6 (5th July 2018) - Mao, Guofeng; Tian, Jiaxin; Li, Ting; Fouad, Hatem; Ga'al, Hassan; Mo, Jianchu
Abstract: The attraction of parasitoids to their hosts is a key issue in efforts to enhance biological control efficiency. This study was conducted to identify which rice plant volatiles are attractive to females of the rice planthopper egg parasitoid Anagrus nilaparvatae Pang et Wang (Hymenoptera: Mymaridae) by using Y‐tube olfactometer behavior assays. Our results demonstrated that 10 of 17 selected volatiles – that is, 3‐carene, linalool oxide, linalool, benzyl alcohol, benzaldehyde, methyl salicylate, ( E )‐2‐hexenal, ( E )‐2‐hexen‐1‐ol, ( E )‐3‐hexen‐1‐ol, and hexanal – from three major groups of rice plant volatiles – terpenoids, aromatic compounds, fatty acid derivatives – attracted female A. nilaparvatae at various doses. Two full‐component mixtures of 10 behaviorally active compounds at different ratios were more attractive to wasps compared with individual volatiles. Blends composed of the 10 behaviorally active compounds in their optimally attractive doses (i.e., each in the dose that elicited the strongest response in the wasps) or at equal mass ratio may be considered as attractants for A. nilaparvatae and thus help to control rice planthoppers. Abstract : The attraction of parasitoids to their hosts is a key issue in efforts to enhance biological control efficiency. Ten of 17 selected volatiles from three major groups of rice plant volatiles attracted female Anagrus nilaparvatae (Hymenoptera: Mymaridae). Synthetic blends of these 10 behaviorally active compounds attracted A. nilaparvatae effectively.